2005
DOI: 10.1111/j.1462-5822.2005.00539.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus anthracis oedema toxin as a cause of tissue necrosis and cell type-specific cytotoxicity

Abstract: SummaryOedema factor (OF) and protective antigen (PA) are secreted by Bacillus anthracis , and their binary combination yields oedema toxin (OT). Following PAmediated delivery to the cytosol, OF functions as an adenylate cyclase generating high levels of cAMP. To assess OT as a possible cause of tissue damage and cell death, a novel approach was developed, which utilized a developing zebrafish embryo model to study toxin activity. Zebrafish embryos incubated with OT exhibited marked necrosis of the liver, cran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 32 publications
1
46
4
Order By: Relevance
“…[24][25][26]. Previous studies have shown that PA can target multiple tissues within the zebrafish (27,28). As shown in Fig.…”
Section: Delivery Of the Tcdb Enzymatic Domain With A Surrogate Systemmentioning
confidence: 82%
“…[24][25][26]. Previous studies have shown that PA can target multiple tissues within the zebrafish (27,28). As shown in Fig.…”
Section: Delivery Of the Tcdb Enzymatic Domain With A Surrogate Systemmentioning
confidence: 82%
“…Like patients, our primates receive antibiotics, and PA antigen was low to undetectable after 24 hours, yet animals challenged with 0.5 to 1.6 ϫ 10 9 CFU/kg still succumbed in 3 to 4 days. Edema toxin will induce necrosis in a zebra fish model, 67 and high doses of edema toxin induce multiple organ failure secondary to vascular permeability changes in mice. 68 In the baboons, necrosis was not observed in the lungs but was present in the adrenals and in kidneys secondary to microthrombosis (not shown).…”
Section: Discussionmentioning
confidence: 99%
“…rEF and rLF proteins were produced as amino-terminal His 6 -tagged proteins as previously described (31,36). Cultures of BL-21/pET15b (containing LF and EF cDNA from B. anthracis) were grown in Luria broth containing ampicillin (50 g/ml) to an optical density at 600 nm (OD 600 ) of 0.6 to 0.8, and protein expression was induced by addition of 1 mM isopropyl ␤-D-thiogalactoside (IPTG) overnight at 16°C.…”
Section: Methodsmentioning
confidence: 99%